A very merry Christmas - Atlantyca (Firm) (New York : Scholastic, 2008)
When Geronimo travels to New York City for Christmas, he accidentally switches luggage with another passenger, so he travels all over the city searching for the bag's owner and his own bag, which contains his Christmas presents.
"English translation ... by Atlantyca S.p.A."--T.p. verso.
Keywords: Mice -- Fiction; Journalists -- Fiction; Christmas -- Fiction; Lost and found possessions -- Fiction; Humorous stories; Mice -- Fiction; Journalists -- Fiction; Christmas -- Fiction; Lost and found possessions -- Fiction; Humorous fiction; Stilton, Geronimo (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Christmas -- Juvenile fiction; Stilton, Geronimo (Fictitious character) -- Fiction; New York (N.Y.) -- Fiction